The neuronal and molecular basis of quinine-dependent bitter taste signaling in Drosophila larvae - Apostolopoulou, Anthi A.; Mazija, Lorena; Wüst, Alexander; Thum, Andreas S. (Frontiers in Behavioral Neuroscience, 2014)
Bitter sensing can alert an animal that a specific type of food is potentially harmful for the organism and should not be consumed. However, not all bitter compounds are equally toxic and some bitter tastants may even have a positive valence in certain contexts, such as self-medication. Thus, taste systems in general have likely a higher capacity than just alerting the animal. In this study, we investigate bitter sensing and processing in Drosophila larvae, using quinine, a substance perceived by humans as bitter. We show that the four different behaviors choice, feeding, survival and associative olfactory learning are directly affected by quinine. On the cellular level we show that only 12 gustatory sensory receptor neurons expressing both GR66a and GR33a are required for quinine dependent choice and feeding behavior. Interestingly these neurons are not necessary for quinine dependent survival or associative learning. On the molecular level, only the GR33a receptor but not GR66a is required for quinine dependent choice behavior. Screening for single gustatory sensory receptor neurons that trigger quinine dependent choice behavior revealed that a single GR97a positive neuron located in the peripheral terminal sense organ is necessary and sufficient. Taken together, our study shows for the first time that the elementary chemosensory system of the Drosophila larva can serve as a simple model to understand the neuronal basis of taste information processing on the single cell level with respect to different behavioral outputs.